Enhancing green innovation performance: the impact of green entrepreneurial orientation and green dynamic capability - Novianty, Rozalina (Institute of Computer Science (IOCS), 2024)
This research explores the importance of green entrepreneurial orientation and green dynamic capabilities in driving green innovation performance in the context of Indonesia's waste management challenges. Through a systematic literature review, this research examines the interaction between these variables and their influence on environmental innovation. The results show that green entrepreneurial orientation has an impact on green dynamic capabilities. Green entrepreneurial orientation plays a key role in strengthening firms' green dynamic capabilities with a focus on environmental sustainability. Furthermore, green entrepreneurial orientation affects green innovation performance. By prioritizing sustainability as one of the main objectives, firms are directed to find business-effective solutions that also consider their impact on the environment. In addition, green dynamic capability orientation affects green innovation performance. Green dynamic capability orientation, which includes a firm's ability to manage change, learn from its environment, and adapt to create environmentally sustainable value, has a significant impact on green innovation performance